FRAKSI PEPTIDA ANTIOKSIDAN DARI KASEIN SUSU KAMBING - Diana Lestari; Joshua Evan; Maggy Thenawidjaja Suhartono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2020)
Milk bioactive peptides are derivative of milk protein produced either through enzymatic activity, digestive processes, or fermentation, that give functional properties. The study aimed to obtain bioactive peptides fraction derived from goat’s milk casein through hydrolysis by papain, analyze the profiles of protein and peptides, and also test the antioxidative activity. The casein isolate was hydrolyzed by papain in a ratio of 100: 0.5 (v/v) at pH 7.0 and 50ºC. Analysis of protein concentration was carried out by the Bradford method and protein profile by SDS-PAGE. Antioxidant assay was carried out by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. A 1,000 ppm ascorbic acid solution was used as positive control. Peptide fractionation was done by membrane filtration with a cut off of 10 kD and 30 kDa. The protein concentration of casein hydrolysates decreased significantly after hydrolysis process with papain. The electrophoresis results showed six protein bands in casein with molecular weight of 7-33 kDa. After the hydrolysis process, all hydrolysates only contained two protein bands with molecular weights of 8 and 5 kDa. The hydrolysis process increased the antioxidant activity of the casein. P0 and P2 hydrolysates had the highest antioxidant activity, and fractions with the highest antioxidant activity were fraction <10 kDa from P0 hydrolysate at 67.89% and 10-30 kDa from P2 hydrolysate at 73.82%. Molecular weight and hydrolysis time affected the antioxidant activity of the hydrolysates. Peptides below 30 kDa have antioxidant activity, whereas those above 30 kDa do not have any antioxidant activity. The antioxidant activity of the peptides decreases upon hydrolysis for more then 2 minutes.